Module Changeability On Software Quality Measurement Of Municipal Government Inventory System - Fadlillah, Fikri (Journal of Informatic and Information Security, 2020)
Inventoring have a function to report the budget realization in the municipal region. SIMSEDIA is an application that helps SKPD on Pekalongan city shall administer the inventory. The purpose of this study was to measure the quality of software SIMSEDIA to determine which features are likely to be developed. The measurement method referring to ISO 9126 models and object-oriented metrics. Measuring the quality specified in the aspect of changeability.The research method consists of:(1) Business Process Review, (2) Module Review, (3) Tools Selection, (4) Modul Measurement, and (5) Result. The results of this study will be a barometer of changeability of SIMSEDIA at the Municipal Government in the development of inventory system to be more optimal. Keywords: coupling, inventory, metrics, module, simsedia